A joint Myxoma in a dog - Millán, Y (2001)
Myxomas of the joints are extremely rare in domestic animals, only four cases, all in dogs, having been reported previously. This paper describes a myxoma originating from the synovium of the right radiocarpal joint of a mature female Dobermann pinscher with right front limb lameness. The tumour was excised surgically and no recurrence was detected during a 2-year follow-up period. Immunohistochemically, the tumour cells reacted with antibodies to vimentin and S100 protein but not with antibodies to cytokeratins (high and low molecular weight) or human callus keratin.